KARAKTERISTIK DAN FAKTOR PENYEBAB PESERTA DIDIK YANG SULIT BERSOSIALISASI DENGAN TEMAN SEBAYA SAAT PEMBELAJARAN DARING - Bela Febriyanti; Yuline Yuline; Amallia Putri (Universitas Tanjungpura, 2021)
AbstractThis study aims to find out why students find it difficult to socialize with peers during online learning. This research uses a qualitative method approach. The source of this research is three students of class X SMA Negeri 7 Pontianak who were determined through purposive sampling techniques. The type of reaserch is intrinsic case study, that using interview, observation and document studies as data collection techniques. Data analysis uses interactive model consist of data reduction, data display, and conclusion drawning. Result of the research shows characteristics of students who difficult to socialize with peers during online learning are not carrying out obligations as students, behaving aggressively, withdrawing from the environment and less communicating. Internal factors that cause difficulty socializing with peers during online learning are rigid personality and lack of confidence while external factors are friendship groups, environment, school and family circumstances. Conclusion of the research is students who lack on socialization with peers during online learning shows distinctive characteristics, the cause of both internal and external factors.Keywords : Characteristics, Difficult on Socialize, Factor, Online Learning, Peers